Coping with work stress : a review and critique - Dewe, Philip J.; O'Driscoll, Michael P.; Cooper, Cary L. (Malden, MA : Wiley, 2010)
Coping With Work Stress: A Review and Critique highlights the most up-to-date research relating to effective coping strategies of individuals and organizations and provides a series of invaluable best practice techniques for dealing with the growing epidemic of stress and lack of overall well-being at work. The authors -- renowned experts in the field -- offer their carefully considered critical reviews of issues surrounding the latest work stress and coping studies and identify several new strategic pathways to stimulate future research.
Includes bibliographical references and index.
Keywords: Job stress; Stress management; työ; stressi; stressinhallinta; jaksaminen